The intracellular loops of the GB2 subunit are crucial for G-protein coupling of the heteromeric gamma-aminobutyrate B receptor - Havlickova, Michaela; Prezeau, Laurent; Duthey, Beatrice; Bettler, Bernhard; Pin, Jean-Philippe; Blahos, Jaroslav (Molecular pharmacology, 2002)
The gamma-aminobutyrate B (GABA(B)) receptor is the first discovered G-protein-coupled receptor (GPCR) that needs two subunits, GB1 and GB2, to form a functional receptor. The GB1 extracellular domain (ECD) binds GABA, and GB2 contains enough molecular determinants for G-protein activation. The precise role of the two subunits in G-protein coupling is investigated. GB1 and GB2 are structurally related to the metabotropic glutamate, Ca(2+)-sensing and other family 3 GPCRs in which the second (i2) as well as the third (i3) intracellular loop play important roles in G-protein coupling. Here, the role of the i2 loops of GB1 and GB2 in the GABA(B) receptor ability to activate G(alpha)-proteins is investigated. To that aim, the i2 loops were swapped between GB1 and GB2 heptahelical domains (HDs), either in the wild-type subunits or in the chimeric subunits GB1/2 that contain the ECD of GB1 and the HD of GB2. The effect of an additional mutation within the i3 loop of GB2 that prevents coupling of the heteromeric receptor was also examined. Combinations of interest were found to be correctly addressed at the cell surface and to assemble into heteromers. Taken together our data revealed the following new information on the G-protein coupling of the heteromeric GABA(B) receptor: 1) the i2 loop of GB2 within the GB2 HD is required for the heteromeric GABA(B) receptor to couple to G-proteins, whereas the i2 loop of GB1 is not; 2) the presence of the i2 loop of GB2 within the GB1 HD is not sufficient to allow coupling of GB1; 3) the GB2 HD activates the Gqi9 protein whether it is associated with the GB2 or GB1 ECD; 4) in the combination with two GB2 HDs, each is able to couple to G-proteins; and finally, 5) the use of mutations in i2, i3, or both within the GB2 HD brings evidence for the absence of domain swapping enabling the exchange of region including i2 and i3 between the subunits.
Keywords: Humans; Recombinant Fusion Proteins; fosfoproteiny; sekvenční homologie aminokyselin; receptory GABA-B; proteiny RGS; podjednotky proteinů; Sequence Homology, Amino Acid; Proline; Molecular Sequence Data; Receptors, GABA-B; molekulární sekvence - údaje; sekvence aminokyselin; mutace; Protein Conformation; proteiny vázající GTP; Leucine; lidé; Cells, Cultured; RGS Proteins; Amino Acid Sequence; kultivované buňky; Protein Subunits; rekombinantní fúzní proteiny; Mutation; prolin; terciární struktura proteinů; Protein Structure, Tertiary; Phosphoproteins; GTP-Binding Proteins; leucin; konformace proteinů